Singlet Oxygen in Lithium−Oxygen Batteries. Issue 2 (1st December 2020) - Hong, Misun; Byon, Hye Ryung
Abstract: Singlet oxygen ( 1 O2 ) is one of the most critical species leading to parasitic side reactions and poor reversibility in non‐aqueous Li−O2 batteries. 1 O2 is generated via the disproportionation of the superoxide radical (O2 .− ) in O2 /Li2 O2 electrochemistry. The mechanistic and computational studies on 1 O2 formation revealed the significant roles of the associated cations, solvation ability of aprotic solvents, H + source, and catalyst/electrode materials. Along with efforts to alleviate 1 O2 production, trapping and eliminating 1 O2 have been attempted using molecular agents. Anthracene derivatives trap 1 O2 and form endoperoxides, which can be quantitatively detected using in situ fluorescence analysis. Physical quenchers that convert 1 O2 to 3 O2 are desirable for cycling of Li−O2 cells because quencher molecules are reusable. We highlight the recent reports on the formation and elimination of 1 O2, and challenges and perspectives of suppressing the 1 O2 effect on the performance of Li−O2 cells. Abstract : The limiting species : Singlet oxygen ( 1 O2 ) is one of the critical species leading to side reactions and poor cyclability of non‐aqueous Li−O2 battery. This minireview covers recent achievements on the major factors determining 1 O2 formation and development of 1 O2 trapping/quenching agents for improving the reversibility of Li−O2 electrochemistry.